1993
DOI: 10.1164/ajrccm/148.3.713
|View full text |Cite
|
Sign up to set email alerts
|

Sudden-Onset Fatal Asthma: A Distinct Entity with Few Eosinophils and Relatively More Neutrophils in the Airway Submucosa?

Abstract: To determine the histologic differences in the airways of patients who died from sudden-onset asthma and the more common slow-onset asthma, we studied seven cases of fatal asthma. The numbers of eosinophils and neutrophils, as well as extracellular deposition of their respective granule contents in the airway mucosa and submucosa, were determined and statistically analyzed. Four of the seven patients had slow-onset asthma attacks in which the time interval between onset of asthma and death was more than 2.5 h.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
306
3
11

Year Published

1995
1995
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 554 publications
(341 citation statements)
references
References 21 publications
18
306
3
11
Order By: Relevance
“…It is possible that the increased numbers of eosinophils in the cases of fatal asthma is due to factors related not only to severity but also to a final episode of asthma. SUR et al [20] have shown that cell profiles in the airway wall may be temporally related to a fatal attack of asthma, and we have recently confirmed these findings [39]. In both studies, neutrophils were observed in much smaller numbers than lymphocytes and eosinophils in cases of fatal asthma, and may be important in the pathogenesis of a fatal attack of asthma.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It is possible that the increased numbers of eosinophils in the cases of fatal asthma is due to factors related not only to severity but also to a final episode of asthma. SUR et al [20] have shown that cell profiles in the airway wall may be temporally related to a fatal attack of asthma, and we have recently confirmed these findings [39]. In both studies, neutrophils were observed in much smaller numbers than lymphocytes and eosinophils in cases of fatal asthma, and may be important in the pathogenesis of a fatal attack of asthma.…”
Section: Discussionsupporting
confidence: 82%
“…In cases of fatal asthma, the numbers of eosinophils were more closely related to the number of lymphocytes than in the nonfatal asthma and control cases. Numerous studies [3,12,15,16,19,20,24,[32][33][34] have shown increased numbers both of lymphocytes and eosinophils in asthmatic airways, although not over the range of asthma severity and airway sizes sampled in this study. It has been suggested that cell/ endothelial adhesion mechanisms and chemoattractant cytokines [35][36][37][38] may provide a common pathway of extravasation for lymphocytes and eosinophils at sites of inflammation.…”
Section: Discussionmentioning
confidence: 52%
“…The asthmatic inflammatory response consists of infiltration into the airway of a variety of activated inflammatory cells with release of mediators of asthma pathophysiology. The eosinophil has an established role as an effector cell in asthma but the pro-inflammatory role of other granulocytes, in particular the neutrophil, remains less well defined [1,2].Increased numbers of airway neutrophils have been described in severe steroid-dependent asthma, during acute exacerbations and in cases of sudden-onset fatal disease [3][4][5]. An increase in neutrophil activation, but not numbers, in mild chronic asthma has previously been shown [6].…”
mentioning
confidence: 99%
“…Increased numbers of airway neutrophils have been described in severe steroid-dependent asthma, during acute exacerbations and in cases of sudden-onset fatal disease [3][4][5]. An increase in neutrophil activation, but not numbers, in mild chronic asthma has previously been shown [6].…”
mentioning
confidence: 99%
“…In addition, neutrophils are a predominant leukocyte present upon histopathologic postmortem examinations of airways of patients with fatal asthma (6,7), and they produce several proinflammatory mediators such as cytokines, proteases, oxygen metabolites, and prostanoids (8). Our understanding of the mechanisms regulating the trafficking of neutrophils to the lungs during Ag-induced inflammation is poor.…”
mentioning
confidence: 99%